Rape Endemic in Nigeria: Causes, Effect and Probable Way Out (Global Journal of Human-Social Science, 2017)
Nigeria faces a number of problems such as high rate of corruption increasing unemployment persistent poverty lack of basic medical care amongst others Added to the above stated developmental problems is the problem of incessant rape permeating the Nigerian society This paper examines the causes and effects of rape The paper is essentially library research with internet sources using expository and phenomenological designs Rape is shown to be a global social problem and its perpetrators cut across all age brackets The paper recommends amongst others that the society should exhibit zero tolerance to rape by engaging rape intolerance attitudes an increased level of empathy every perpetrator of rape should be exposed to take full responsibility for his or her actions and should under no circumstances be shielded or protected by parents colleagues or churches Nigerian government should enforce laws to protect women against rape
Keywords: rape; girl; sex; nigeria; control